2007
DOI: 10.1021/pr070087o
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Endometrial Tissue Biomarkers Previously Discovered Using Mass Spectrometry-Based Proteomics by Means of Immunohistochemistry in a Tissue Microarray Format

Abstract: Verification of candidate protein biomarkers is a necessary step in moving from the initial discovery to application. Here, we report results of a verification exercise involving six candidate endometrial cancer biomarkers previously discovered using mass-tagging and multidimensional liquid chromatography/tandem mass spectrometry (DeSouza L., et al. J. Proteome Res. 2005, 4, 377-386) on a cohort of 148 patient samples by means of immunohistochemistry on a tissue microarray format. A panel of the three best-per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…18 AAT has been found to be associated with a number of cancers, including lymphoma and cancers of the liver, lung, stomach, bladder, gall-bladder, 54,55 and endometrium. [18][19][20] MIF has been found to be overexpressed in a number of cancers, including endometrial, 18 hepatocellular, 56 non-small-cell lung, 57 and brain. 58,59 In addition to the above, a number of proteins that have been linked to other cancers have also been identified in this study.…”
Section: Identification Of Proteins Known To Be Associated With Cancersmentioning
confidence: 99%
“…18 AAT has been found to be associated with a number of cancers, including lymphoma and cancers of the liver, lung, stomach, bladder, gall-bladder, 54,55 and endometrium. [18][19][20] MIF has been found to be overexpressed in a number of cancers, including endometrial, 18 hepatocellular, 56 non-small-cell lung, 57 and brain. 58,59 In addition to the above, a number of proteins that have been linked to other cancers have also been identified in this study.…”
Section: Identification Of Proteins Known To Be Associated With Cancersmentioning
confidence: 99%
“…This complicated interplay of factors leading to neoplastic progression is ultimately reXected in the protein expression proWles of cells. Thus, study of these proWles can reveal speciWc biomarkers for cancer (Roeßler et al 2005;Melle et al 2005;Xing et al 2006;Rosty et al 2002;Dube et al 2007). Biomarkers are the speciWc protein products of active genes, which represent the molecular characteristic or signature of cells (Aung et al 2006;Srinivas et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few proteomic studies on EC have been reported; however, some of the findings seem to be noteworthy and have been verified by immunohistochemical assays. 2,3 These studies reported slightly different findings and conclusions, which might be due to ethnic differences among patients or technical problems such as varying ability of mass spectrometry (MS) identification.…”
mentioning
confidence: 99%